Development of wedding planner prototype / Mazlinda Ismail - Ismail, Mazlinda (2005)
Recommendation system is a system which provides a recommendation, prediction or opinion that can assist the user in computerized solution. Recommendation system is one of the areas where the application of Expert System is gaining momentum. Wedding planner prototype has been developed using expert system to support wedding area service. The system is to verify the suit wedding wear and wedding dais design for Malay women in Malaysia. This system used Rule-based (RB) approach to achieve the objectives. Forward chaining (FC) and backward chaining (BC) are the two techniques that being used to get the result. The analysis and comparison of wedding wear and dais are based on wedding theme and relevant inputs. . From the knowledge acquisition, the information filtered and being grouped and the relationship between data are determined. The result deployed as information in the system to guide and recommend to the Malay women about appropriate wedding wear and dais that follow user requirements. A computational result which is the most valuable from among the available solution is presented. Even though the system has been successfiilly developed, it still have several weaknesses such as the result for the system may is not enough where, it is limited to wedding wear and wedding dais design. Besides, this system may allow one user using the system at one time because of the system has been developed for stand-alone environment, hi future, I would recommend the results viewed can be expanding based on costs, venue or list of guests, not limited to the wedding wear and wedding dais design. The study should be implying in the fiiture by expanding the scope to Malay men and other races in Malaysia.